Perspectives of the well-educated commercial sex workers in Iloilo City on why they opted to do sex work - Terania, Joeylyn Hingco (University of the Phllippines Visayas, 2021)
The Philippines has significant made development in the enhancement and availability of opportunities and welfare for women. Depite these changes there are still an existing wide gap between men and women due to the system of patriarchy.Issues like commodification, objectification, sexual abuse, and exploitation are some of the many struggles' women have experienced.Women who engaged in sex work are considered highly vulnerable due to the nature of their income source intertwined with danger of abuse and exploitation from their client who are mostly men. These research recognized the importance of Commercial Sex Workers (CSW) perspectives for they are a primary source of narrative to effectively convey their experiences. As a result of this study, it showed that CSW opted to do sex work due to economic needs and their educational attainment are not enough to access competitive salaries, safer jobs, and benefits. The labor market requires high qualifications, experiences, and skills. In addition to this, trainings, certificates, seminars, units of specialization that is relevant to their line of work are needed. This entails additional financial needs which is not a priority to people who are trying to provide and survive daily.